2003
DOI: 10.1007/s00134-003-1748-5
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation as a bridge to cardiac transplantation in a patient with cardiomyopathy and hemophilia A

Abstract: We report the successful use of ECMO as a bridge to cardiac transplantation in a patient with hemophilia A and low-level factor VIII inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“… 115 Not surprisingly, relative to similar procedures in the general population, cardiac operations in PWH incur substantially increased costs (primarily due to hemostatic treatments) and resource utilization. 115 , 123 , 126 Advance planning and involvement of a multidisciplinary team serves to optimize clinical outcomes while minimizing risk.…”
Section: Cardiovascular Conditions Requiring Operations In People Witmentioning
confidence: 99%
See 1 more Smart Citation
“… 115 Not surprisingly, relative to similar procedures in the general population, cardiac operations in PWH incur substantially increased costs (primarily due to hemostatic treatments) and resource utilization. 115 , 123 , 126 Advance planning and involvement of a multidisciplinary team serves to optimize clinical outcomes while minimizing risk.…”
Section: Cardiovascular Conditions Requiring Operations In People Witmentioning
confidence: 99%
“…Importantly, the accuracy of ACT monitoring is uncertain unless there are near-normal factor levels. 126 In addition, the utility and accuracy of ACT monitoring during CPB when using hemostatic coverage with bypassing agents is uncertain. For monitoring hemostatic therapy during cardiac surgery (with or without CPB), the measurement of PTT or factor levels is a viable option.…”
Section: Cardiovascular Conditions Requiring Operations In People Witmentioning
confidence: 99%
“…A review of the literature revealed case reports of heart transplant in HA patients were limited to a 63‐year‐old man 7 and four children ages 5, 12, 14, and 15 (Table S1). 8–11 Two patients required VAD and two patients were on ECMO, before and/or after the procedure. Interestingly, two patients developed heart failure secondary to cardiac infarcts/thromboses after receiving activated prothrombin complex concentrate 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with multiple organ failure from any etiology, septic shock, burns, trauma, airway abnormalities requiring complicated surgical repair, and immunocompromised patients all represent categories of disease that would have precluded ECMO use in the past but have been successfully supported with ECMO in more recent years. [5][6][7][8][9][10][11][12] Neonates While neonates with respiratory failure have formed the largest group of ECLS patients, advancement in prenatal and perinatal care, coupled with therapies and techniques such as inhaled nitric oxide, surfactant replacement, and high-frequency ventilation, have reduced the need for ECLS in many neonates with respiratory failure. 13 Recognition and resolution of persistent pulmonary hypertension of the newborn with some of the therapies mentioned has decreased the need for ECLS in such patients.…”
Section: Patient Populations Treated With Eclsmentioning
confidence: 99%